Pengaruh Teknologi Gadget bagi Generasi Gen-Z: Penelitian - Maria Magdalena Bate'e; Tiarni Duha; Verdian Christian Telaumbanua; Herniwati Giawa; Heribertus Arlindu Halawa; Herman Kurniawan Ndruru; Aluizatulo Halawa; Nofamataroeli Lahagu (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The advancement of gadget technology in the digital era has had a significant impact on the behavior of Generation Z. Gadgets now function not only as communication tools, but also as educational, entertainment, and social media. This study aims to explore the positive and negative impacts of gadget use on mental health, social interactions, and academic performance of Generation Z. Through an online survey of 350 respondents from among young students and college students, data were analyzed descriptively and correlationally. The results of this study indicate that although gadgets support access to information and online social interactions, excessive use can trigger stress, sleep disorders, and digital addiction. Therefore, education is needed on the wise use of technology so that its benefits are optimal and its negative impacts can be minimized.